Ritual and ritual text in the Zoroastrian tradition: the extent of Yasna 41 - Zeini, A (Cambridge University Press, 2021)
This article examines the extent of the concluding section (Y 41) of the Yasna Haptaŋhāiti in light of the manuscript evidence and the section's divergent reception in a Middle Persian text known as the “Supplementary Texts to the Šāyest nē Šāyest” (Suppl.ŠnŠ). This investigation will entertain the possibility of an alternative ritual being described in the Suppl.ŠnŠ. Moreover, it argues that the manuscripts transmit the ritual text along with certain variations and repetitions while the descriptions of the extent of each section preserve the necessary boundaries of the text as a textual composition or unit.